Mothers Information Regarding Asthmatic Child Care in Kirkuk City - ameen, Blend (Iraqi National Journal of Nursing Specialties, 2015)
Objectives: To assess the information of mothers regarding asthmatic child care, and to find out the relationship between information of mothers and some of demographic characteristic such as age of mothers, Level of education, and away of child feeding. Methodology: Quantitative design (a descriptive study) was conducted in pediatric hospital in Kirkuk city from the period of first of July 2011 to the end of March 2012. To achieve the objectives of the study, non probability sample of (50) mothers having asthmatic children who attend to the pediatric hospital. The data are collected through utilization of constructed questionnaire. It consists of two parts: part one include (8) items, about demographic characteristics of mothers and her children and part two include (26) items, which includes (3) sections, section (1) consist of (7) items, about aggravating factors of asthma, section (2) consist of (6) items, about symptom of sever attack of asthma, and section (3) consist of (13) items, about asthmatic child care. To content validity of instrument was established through penal of (5) expert. Data I collected by interview technique using the questionnaire, data I gathered and analyzed by the application of descriptive and inferential statistics methods. Results: The study indicated that the majority of children are aged between (1-3) years old, and highest percentage of children are male (62%). Regarding to the child feeding, the majority of children are food feeding and represent (48%). Regarding age of mother the study finding that the highest percentage (38 (% of the mothers their age group between (23-27) years, and concerning mothers’ educational level, the majority of them graduated from primary school (40%). The study also approves that there was a statistical significant association between mother's information and some of demographic characteristic such as (Age, and level education of mothers and way of child feeding). Recommendation: Education program should be provided to the mothers who have children with asthma and course training program should be developed and implemented.